Efficacy and safety of edoxaban in patients with diabetes mellitus in the ENGAGE AF-TIMI 48 trial. (1st April 2020) - Plitt, Anna; Ruff, Christian T.; Goudev, Assen; Morais, Joao; Ostojic, Miodrag C.; Grosso, Michael A.; Lanz, Hans J.; Park, Jeong-Gun; Antman, Elliott M.; Braunwald, Eugene; Giugliano, Robert P.
Abstract: Background: Diabetes mellitus is an independent risk factor for stroke and atrial fibrillation. Therefore, the risk/benefit profile of the oral factor Xa inhibitor edoxaban stratified by diabetes is of clinical interest. Methods: 21, 105 patients enrolled in ENGAGE AF-TIMI 48 were stratified into 2 pre-specified groups: without (N = 13, 481) and with diabetes (N = 7, 624). Results: On average, patients with diabetes were younger, and had a higher body mass index, CHA2 DS2 -VASc score and baseline endogenous Factor Xa activity. After multivariate adjustments, patients with diabetes had a similar rate of stroke and systemic embolism compared to those without diabetes (adjusted hazard ratio (HRadj ) 1.08; 95% confidence interval (CI) 0.94–1.24; p = 0.28). However, the risk of major bleeding was significantly higher in patients with diabetes (HRadj 1.28; 95% CI 1.14–1.44; p < 0.001). The treatment effect of edoxaban (vs warfarin) was not modified by diabetes (all p-interactions > 0.05), a finding supported by the preserved edoxaban concentrations and inhibition of Factor Xa regardless of diabetes. The HRs of stroke and systemic embolism in patients receiving the higher-dose edoxaban regimen vs warfarin were 0.93 and 0.84 (p-interaction = 0.54) in those with and without diabetes respectively. The higher-dose edoxaban regimen reduced major bleeding (by 19–21%) and cardiovascular death (by 7–17%) regardless of diabetes (p-interactions = 0.81 and 0.33 respectively). Conclusion: Patients with diabetes in ENGAGE AF-TIMI 48 had higher bleeding risk, but after adjustment similar stroke risk, compared to those without diabetes. The higher-dose edoxaban regimen had similar efficacy compared to warfarin, while reducing bleeding and cardiovascular mortality, irrespective of diabetes. Highlights: In this sub-analysis of the ENGAGE AF-TIMI 48 trial patients with diabetes were more prone to bleeding. The approved edoxaban regimen reduced major bleeding and CV death, while achieving similar protection from thromboembolism. The pharmacokinetic and pharmacodynamic results of edoxaban were consistent regardless of the diabetes status.